2007
DOI: 10.1590/s0102-695x2007000200018
|View full text |Cite
|
Sign up to set email alerts
|

Atividades farmacológicas dos extratos de Zanthoxylum chiloperone (Rutaceae)

Abstract: RESUMO:Neste trabalho foram avaliadas as atividades antinociceptiva e antiinfl amatória dos extratos das folhas de Zanthoxylum chiloperone. Os ensaios foram realizados pelos testes de contorções abdominais induzidas por ácido acético, tempo da lambida da pata induzida por formalina, edema de pata e pleurisia induzidas por carragenina, usando os extratos hexânico, em acetato de etila e etanólico administrados nas doses de 100 e 200 mg/kg. As doses testadas reduziram, signifi cativamente, as contorções abdominai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
7
0
5
Order By: Relevance
“…They have been employed in the treatment of infl ammatory diseases, malaria, snakebite, toothache, tuberculosis, not to mention their antimicrobial activity (Jullian et al, 2006;Villalba et al, 2007). Zanthoxylum naranjillo Griseb., known in Brazil as 'juva', 'naranjillo', 'tembetari', and 'espinilho', is used in Brazil as a folk medicine against illnesses associated with infl ammatory processes (Reitz, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…They have been employed in the treatment of infl ammatory diseases, malaria, snakebite, toothache, tuberculosis, not to mention their antimicrobial activity (Jullian et al, 2006;Villalba et al, 2007). Zanthoxylum naranjillo Griseb., known in Brazil as 'juva', 'naranjillo', 'tembetari', and 'espinilho', is used in Brazil as a folk medicine against illnesses associated with infl ammatory processes (Reitz, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…Graphs and IC 50 values and their respective 95 % confidence limits (95 % LC) were prepared using the PrismGraphPad6 software. The genus Zanthoxylum is described in the literature as having other activities of biological interest, such as leishmanicidal 13 , antimicrobial and antinociceptive activity 14 , allowing a deeper analysis of the genus Zanthoxylum Although the phytochemical analysis demonstrates the presence of coumarins, a toxic metabolite, the cytotoxicity analysis by the MTT assay demonstrated that the aqueous extract of Z. tingoassuiba is non-toxic at concentrations of 5 mg/mL and its serial dilutions. The comparison with the negative control (NC) shows that in 5 mg/mL the viability of PBMCś reaches almost 100 %.…”
Section: Discussionmentioning
confidence: 99%
“…The study carried out with Z. chilipirone shows that with doses of 100 and 200 mg/kg of each extract is possible to detect significantly inhibition in the paw lick, results that suggest that the extracts from Z. chiloperone possess constituents with antinociceptive activity (Villalba et al, 2007). Moreover, the study with extracts of Z. rhoifolium sought to confirm its popular use, and shows for the first time that ethanol extract of Z. rhoifolium stem bark, its fractions and one of the major constituents (lupeol) have antinociceptive activity when administered orally in different models of chemical nociception in mice (Pereira et al, 2010).…”
Section: Antinociceptive Activitymentioning
confidence: 97%
“…In different studies, ethanolic extracts of bark from Z. elephantiasis, Z. fagara, Z. martinicense and Z. coriaceum, and hexane, ethyl acetate and ethanolic extracts of leaf from Z. chiloperone have presented promising results of antiinflammatory activity (Villalba et al, 2007;Márquez et al, 2005;Bastos, 2001). …”
Section: Anti-inflamatory Activitymentioning
confidence: 99%